PENGEMBANGAN MODUL PEMBELAJARAN BIOLOGI BERMUATAN STUDI KASUS PADA MATERI EKOSISTEM UNTUK SISWA SMA/MA KELAS X - Natalia, Desfaur; Lufri, Lufri; Sumarmin, Ramadhan (Kolaboratif, 2014)
One of the reasons for low success in studies is the variation in the teaching methods and few teaching materials, especially ecosystem matter, thus producing poorly motivated students with low esteem to learn on their own depending on individual ability. The purpose of this research was to develop a Biology learning module containing case study on Ecosystem topics for the first year students of Senior High School which was valid, practical and effective This was a developmental research which used Plom model that consisted of three phases including 1) preliminary investigation phase, 2) planning and realization phase, and 3) try-out and evaluation phase. In the initial investigation phase, an interview and observation were done to identify the problems in learning. Further, analysis of curriculum, analysis of students and analysis of learning sources were conducted. In the planning and realization phase, the module was designed and it then was validated by experts (lecturers and teachers). The practicability was measured by filling in the practicality questionnaire which was done by the teacher and the students. The effectiveness of the module developed was seen through observation and the students’ learning achievement. The students’ achievement in learning was seen through daily tests. The data gotten was analyzed descriptively. The research results showed that the developed module is valid from didactic, structural, and technical aspects. From the practicability stage, it was found out that the module is practical. The use of the module can make a student active in learning with a high percentage passing the school-set minimum grade (KKM), whereby 90% of students at SMAN 10, Tebo district scoring ≥ 78 with 93% of their counterparts at SMAN 8, Tebo district scoring ≥ 75. It can, therefore, be concluded that the developed Biology learning module containing case studies on Ecosystem topics for the First Year students of Senior High School had been valid, practical and effective to be used as the learning materials.